Minimally Invasive Aortic Valve Replacement in Contemporary Practice: Clinical and Hemodynamic Performance from a Prospective Multicenter Trial - Velders, Bart J.J.; Vriesendorp, Michiel D.; Reardon, Michael J.; Rao, Vivek; Lange, Rüdiger; Patel, Himanshu J.; Gearhart, Elizabeth; Sabik, Joseph F., III; Klautz, Robert J.M. (The Thoracic and Cardiovascular Surgeon, 2022)
Background The advent of transcatheter aortic valve replacement (AVR) has led to an increased emphasis on reducing the invasiveness of surgical procedures. The aim of this study was to evaluate clinical outcomes and hemodynamic performance achieved with minimally invasive aortic valve replacement (MI-AVR) as compared with conventional AVR.Methods Patients who underwent surgical AVR with the Avalus bioprosthesis, as part of a prospective multicenter non-randomized trial, were included in this analysis. Surgical approach was left to the discretion of the surgeons. Patient characteristics and clinical outcomes were compared between MI-AVR and conventional AVR groups in the entire cohort (n = 1077) and in an isolated AVR subcohort (n = 528). Propensity score adjustment was performed to estimate the effect of MI-AVR on adverse events.Results Patients treated with MI-AVR were younger, had lower STS scores, and underwent concomitant procedures less often. Valve size implanted was comparable between the groups. MI-AVR was associated with longer procedural times in the isolated AVR subcohort. Postprocedural hemodynamic performance was comparable. There were no significant differences between MI-AVR and conventional AVR in early and 3-year all-cause mortality, thromboembolism, reintervention, or a composite of those endpoints within either the entire cohort or the isolated AVR subcohort. After propensity score adjustment, there remained no association between MI-AVR and the composite endpoint (hazard ratio: 0.86, 95% confidence interval: 0.47–1.55, p = 0.61).Conclusion Three-year outcomes after MI-AVR with the Avalus bioprosthetic valve were comparable to conventional AVR. These results provide important insights into the overall ability to reduce the invasiveness of AVR without compromising outcomes.
Keywords: aortic valve replacement; minimally invasive; surgical techniques